Impact of pharmaceutical care on the follow-up of patients with chronic diseases in a primary health care unit in the city of São Luís-MA - Leal, Yuri de Melo; Alencar , Maysa Souza de; Cardoso , Vinícius Lagos; Queiroz, Paulo Victor dos Santos; Melo , Thamys Marinho; França , Lucas Martins; Pinto , Bruno Araújo Serra; Flister , Karla Frida Torres (Seven Editora, 2023)
In Pharmaceutical Care, pharmacists collect and evaluate  information about the patient, including the identification of possible Drug-Related Problems (DRPs), in  addition to encouraging self-care and promoting better pharmacotherapy. The objective was to evaluate the  impact of pharmaceutical care on the quality of life of a patient with breast cancer and metabolic syndrome.  Pharmacotherapeutic follow-up was carried out for one semester. In the meantime, adherence (BaMQ),  degree of depression (PHQ-9) and quality of life (SF-36) of the patient were evaluated before, during and  after the interventions. Patient undergoing chemotherapy for breast cancer, undergoing treatment for  diabetes, hypertension, dyslipidemia, in addition to practicing self-medication. Before follow-up, he  presented drastic fluctuations in blood glucose and blood pressure, poor eating habits, dyslipidemia,  sedentary lifestyle and complaints of pain. After the interventions, he showed a relative improvement in the  metabolic syndrome linked to better life habits, despite the aggressive treatment of chemotherapy. The interventions carried out during the pharmaceutical follow-up had positive impacts, which reinforces the  importance of the pharmacist in satisfactory primary care and health promotion. DOI:https://doi.org/10.56238/innovhealthknow-045